Development of wear resistant hammer heads for coal crushing application through experimental studies and field trials. (February 2019) - Kishore, Kaushal; Adhikary, Manashi; Mukhopadhyay, Goutam; Bhattacharyya, Sandip
Abstract: Coke is one of the most important raw materials for iron making through blast furnace route. Strength and reactivity of coke plays a huge role in efficiency of the counter-current reactor. In order to attain the desired quality of coke, large lumps of coals are crushed in to smaller size fraction in a crushing mill using rotating hammers. However, the heads of these hammers fail prematurely during service that requires their frequent replacements along with interruption in production. This paper presents failure analysis of a coal crushing hammer head with its detailed metallurgical characterization. Analysis revealed that hammer heads fail in abrasive wear mode due to lean chemistry of the alloy used and lower hardness that manifests as higher abrasion rate. 6Cr1Mo steels were supplied in quenched and tempered conditions to a hardness of around 52 HRC. There was presence of only iron chromium carbides that is not sufficient to withstand an application involving extreme wear. The second part of this paper presents detailed chemistry-microstructure-wear resistance correlation for four different alloys; 6Cr1Mo, 20Cr1Mo, complex refractory alloy carbides and tungsten carbide weld deposited hard-facing. Microstructural analysis and phase identification is carried out using scanning electron microscope coupled with electron probe micro-analyzer, x-ray diffraction and Vickers hardness tester. Dry sand abrasion tests were carried out for the existing 6Cr-1 Mo steel and proposed trial specimens. Study shows that the abrasion resistance is strongly a function of type of carbides and their volume fraction. Niobium carbide and tungsten carbides are much more effective in improving the abrasion resistance of alloys compared to primary chromium carbides. Tungsten carbide hard-facing demonstrated the best abrasion resistance. Based on the study, a new design for hammer head with tungsten carbide hard-facing is developed and field trial revealed an improvement in service life greater than three times compared to existing 6Cr1Mo quenched and tempered hammer heads. Highlights: Coal crushing hammer head fail frequently in predominantly abrasive wear mode due to insufficient fraction of chromium carbides. Three different alternatives were proposed, viz., (i) 20 Cr-1 Mo cast alloy, (ii) hard-facing of complex refractory alloy carbides of Cr, Mo and Nb, (iii) WC hard-facing on mild steel. Microstructural analysis was carried out using scanning electron microscope coupled with electron probe micro-analyzer and x-ray diffraction. Abrasion resistance was in the following order: WC hard-facing > complex refractory alloy carbides hard-facing > 20Cr-1Mo cast alloy > existing alloy. Abrasive wear resistance is dictated by chemistry, nature and type of carbides, their morphology and micro-hardness. Actual field trial with WC-hardfaced hammer heads revealed an improvement in service life by >300 % compared to the existing 6Cr-1Mo cast hammer heads.